2020
DOI: 10.3390/antiox9100968
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm in Adipose Tissue: Novel Antioxidant Target for Metabolic and Cardiovascular Diseases

Abstract: Obesity is a major risk factor for most metabolic and cardiovascular disorders. Adipose tissue is an important endocrine organ that modulates metabolic and cardiovascular health by secreting signaling molecules. Oxidative stress is a common mechanism associated with metabolic and cardiovascular complications including obesity, type 2 diabetes, and hypertension. Oxidative stress can cause adipose tissue dysfunction. Accumulating data from both humans and experimental animal models suggest that adipose tissue fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 280 publications
(342 reference statements)
0
20
0
Order By: Relevance
“…Since CLOCK and ARNTL are sensitive to the intracellular redox state [37], this may justify the effect of a pro-oxidative agent such as PM on cellular circadian pathways. Accordingly, 24-h oscillations of H 2 O 2 levels seem to have a modulatory effect on the activity of the CLOCK protein via cysteine oxidation [38]. Secondly, the fine and ultrafine PM may influence the epigenetic regulation of clock genes by stimulating the release of microvesicles by the lung epithelium and inflammatory cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Since CLOCK and ARNTL are sensitive to the intracellular redox state [37], this may justify the effect of a pro-oxidative agent such as PM on cellular circadian pathways. Accordingly, 24-h oscillations of H 2 O 2 levels seem to have a modulatory effect on the activity of the CLOCK protein via cysteine oxidation [38]. Secondly, the fine and ultrafine PM may influence the epigenetic regulation of clock genes by stimulating the release of microvesicles by the lung epithelium and inflammatory cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Living organisms, such as animals, cyanobacteria, and plants, have an internal endogenous oscillator known as the circadian clock, which predicts the alteration during the light and dark cycles. The term “circadian” was first coined in 1959 by Franz Halberg, originated from two different Latin words “circa” means “around” and “diem or dies” means “day” ( McClung, 2006 ; Srivastava et al, 2019 ; Man et al, 2020 ). It permits organisms to synchronize and assemble for daily or seasonal changes depending on the surrounding environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that high artificial light levels, either outdoor or in the bedroom, correlate with increased body weight in adults. This fact might be explained by the exposure to light of shorter wavelengths associated with altered sleep–wake cycle, daily rhythms of food intake, and disturbed metabolism ( 21 , 22 ). However, it is not clear what are the metabolic consequences of chronic screen light exposures in young children.…”
Section: Discussionmentioning
confidence: 99%